PENGGUNAAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN KETERAMPILAN MENGOPERASIKAN APLIKASI CORELDRAW (Single Subject Research Anak Hambatan Pendengaran Kelas VIII di SLB N 1 Padang ) - Syari Yuliana (Jurnal Penelitian Pendidikan Khusus, 2015)
ABSTRAK The research was conducted due to the fact in the field indicating  that a student with hearing impairment named X in class VIII of SLB N 1 Padang got problems in computer class especially to aplly Coreldraw application ti design T-shirt. This research was aimed at increasing the skill of the student with hearing impairment to aplly Coreldraw application through instructional. This reserach Single Subject Research approach to the design of the ABA. Result of this study indicate that that the media instructional video could increase the skill of the student with hearing impairment to aplly Coreldraw application . Kata Kunci: Anak Hambatan Pendengaran, Video Pembelajaran, Aplikasi Coreldraw.